Improvement and Conditions Optimization of a Carbon Dioxide Successive Determining Test Method - Pang, Dao-Lin; Jin, Chao; Li, Fang (Asian Journal of Chemistry, 2013)
A carbon dioxide successive determining method was improved and established for the determination of ultimate aerobic biodegradability of plastic materials under controlled composing conditions. The improvement and optimization of systematic operational conditions which include selection of desiccant, air flow velocity region and charges of absorbent etc., were also studied. Measurement and optimization results confirmed that the system was fitted for designed purpose and more excellent than some reported ways. Those results can be a basement of automating the CO2 and other gas production measurements.